Parametric and non-parametric approaches in evaluating martingale hypothesis of energy spot markets - Cheong, Chin Wen (Elsevier Ltd., 2011)
This study examined the martingale hypothesis in the spot prices of the petroleum products markets. Under the parametric and non-parametric variance ratio tests, the independent and identically distributed increments and less restrictive martingale increments are evaluated over the period 1986-2009. In order to investigate how the energy markets' efficiency evolved over the long spanning data, we had divided them into three sub-periods according to several important events that strongly influenced the energy price movements. The empirical findings of this study can be summarized as follows: First, both the West Texas Intermediate (WTI) crude oil and New York Harbor (NYH) gasoline markets were somewhat informationally inefficient before the North American Free Trade Agreement (NAFTA) and during the Iraqi invasion of Kuwait in 1990. Second, the martingale hypothesis analysis indicated that after the NAFTA regulation and Iraqi invasion, both the energy markets became more efficient which implied that the energy prices fully reflected all available market information. Finally, although the period after 2002 is related to high volatility with an upward trend in energy demand, the well informed energy market participants somehow are able to anticipate the price fluctuations